Presence of Heavy Metals in over the Counter Teeth Whitening Products– An Evaluative Study - Chitra Ravi; Sendhilkumar Muthappan; Manickam Ponnaiah; Deepika Chandrasekaran; Sowmiya Murugavel; Jimson Samson (Indian Journal of Dental Research)
Background: Dentistry plays a crucial role in shaping the facial aesthetics of a person and thus boosts self-esteem. Tooth discolouration is one of the significant cosmetic problems and hence, many teeth whitening products are widely used for discolouration. However, these products may have heavy metals or chemicals that can affect the tooth and other organs. Aim: The aim is to estimate the amount of heavy metals present in teeth whitening products available for purchase over-the-counter in the pharmacies. Materials and Method: A cross-sectional study of teeth whitening products available Over the Counter (OTC) in pharmacies in Chennai and adjoining districts of Tamil Nadu was conducted during the period from December 2019 to February 2020. The Flame Atomic Absorption Spectrometry (FAAS) method was used to measure the heavy metals such as inorganic lead, chromium, cobalt, arsenic, cadmium, nickel and mercury in the products. Results: We collected 39 products and finalized nine for analysis. These products were available as tablet (n = 1), liquids (n = 2) and powders (n = 6). All products were mentioned as herbal or natural. Three products contained inorganic lead levels in parts per million (ppm) of 759 (product 2); 39.4 (product 3) and 28.1 (product 7), way above the permitted levels. None of the other heavy metals were detected from these products. Conclusion: After analysis with the FAAS method, inorganic lead over and above the permissible levels was observed. Dental professionals and community need to be aware of the availability of such products and its detrimental effects on oral and general health.